Knowledge, Attitude and Practices of Osteoporosis Risk Factors among Jazan University Students, 2019 - Khired, Zenat A.; AlHulaibi, Manal; Alhazmi, Alhasan; durayb, Amjad; Mushari , Rawiah; Mahzari , Sarah; Kilani, Wafa; Jawhari, Amani; Alhazmi, Rawan; M. H., Elmahdy (International Journal of Innovative Research in Medical Science, 2022)
Osteoporosis is one of the non-communicable diseases that closely links to lifestyle and nutrition. This is a cross-sectional descriptive epidemiologic study, carried out on 440 Jazan university students (males& females). They are chosen by a stratified multistage cluster sampling technique to assess their knowledge, attitude, and practices (KAP) about osteoporosis risk factors. The data are collected using a validated semi structured Arabic questionnaires. The findings revealed that almost all survey participants agreed with the definition of osteoporosis, which is the decrease of bone density, with only 8.7% disagreeing. Furthermore, 80.0 percent of survey participants classified osteoporosis as a cause of bone fracture. The findings suggest that the study participants' good attitudes toward risk factor prevention of osteoporosis are linked to the daily consumption of an acceptable amount of milk. Another positive attitude toward osteoporosis prevention stemmed from a reduction in the amount of energy drinks consumed, which has been identified as an osteoporosis risk factor. The study recommends that university students of all grades participate in health education programs about osteoporosis risk factors and preventive treatment.